Does the Prevalence of Dyslipidemias Differ between Newfoundland and the Rest of Canada? Findings from the Electronic Medical Records of the Canadian Primary Care Sentinel Surveillance Network - Asghari, Shabnam; Aref-Eshghi, Erfan; Hurley, Oliver; Godwin, Marshall; Duke, Pauline; Williamson, Tyler; Mahdavian, Masoud (Frontiers in Cardiovascular Medicine, 2015)
Introduction: Newfoundland and Labrador (NL) has the highest prevalence of cardiovascular ‎disease (CVD) in Canada. Dyslipidemia is a risk factor for cardiovascular disease. This study ‎compares the prevalence of dyslipidemia in the NL population with the rest of Canada.‎ Methods: A cross-sectional study, using data from the Canadian Primary Care Sentinel ‎Surveillance Network (CPCSSN), was undertaken. The study population included adults, ‎excluding pregnant women, aged 20 years and older. Canadian guidelines were used for ‎classifying dyslipidemia. Univariate and multivariate analyses were conducted to compare the ‎lipid levels and prevalence of dyslipidemia between NL and the rest of Canada.‎ Results: 128,825 individuals (NL: 7,772; rest of Canada‎: 121,053) were identified with a mean ‎age of 59 years (55% Females). Mean levels of total Cholesterol (4.96 vs. 4.93, P=0.03), LDL ‎‎(3.00 vs. 2.90 mmol/L, P<0.0001), triglyceride (1.47 vs. 1.41 mmol/L, P<0.0001), and HDL (1.29 ‎vs. 1.39 mmol/L, P<0.0001) were significantly different in NL compared to the rest of Canada‎. ‎Dyslipidemias of LDL (29% vs. 25% P<0.0001), HDL (38% vs. 27%, P<0.0001), and ‎triglyceride (29% vs. 26%, P<0.0001) were significantly more common in NL. After adjustment ‎for confounding variables, NL inhabitants were more likely to have dyslipidemia of total ‎cholesterol (OR: 1.16, 95% CI: 1.10-1.23, P<0.0001), HDL (OR: 1.52, 95% CI: 1.44-1.60, ‎P<0.0001), LDL (OR: 1.38, 95% CI: 1.30-1.46, P<0.0001), and ratio (OR: 1.53, 95% CI: 1.42-‎‎1.60, P<0.0001).‎ Conclusion: The NL population has a significantly higher rate of dyslipidemia compared to the ‎rest of Canada‎, and the mean levels of all lipid components are worse in NL. Distinct cultural ‎and genetic features of the NL population may explain this, accounting for a higher rate of CVD ‎in NL.‎